2011
DOI: 10.5012/jkcs.2011.55.6.936
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted One-Pot Synthesis of Octahydroquinazolinone Derivatives Catalyzed by Thiamine Hydrochloride Under Solvent-free Condition

Abstract: ABSTRACT. Thiamine hydrochloride (VB1) has been used as an acid catalyst in organic synthesis. One pot three component Biginelli condensation of dimedone, urea/thiourea and substituted aromatic aldehydes catalyzed by 10 mol % of thiamine hydrochloride (VB1) in solvent free condition under microwave irradiation in good to excellent yields has been investigated. Utilization of microwave irradiation, simple reaction conditions, short reaction time, ease of product isolation, and purification makes this manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Biginelli reaction is an efficient one-pot multicomponent condensation reaction that is used widely in organic and medical chemistry (Bose et al, 2005;Kulkarn et al, 2009;Mochaddas et al, 2012). Starting from aldehyde, Urea(thiourea) and β-keto ester under strongly acidic condition represented by Lewis acid to obtaine the pyrimidine-2-one analogs (Kappe, 1993;Mohammadizadeh and Firoozi, 2011), which received a significant attention owing to their biological (Shutalev et al, 1998;Mobinikhaledi and Kalhor, 2010) and pharmaceutical properties (Phucho et al, 2009;Piqani and Zhang, 2011;Shaikh et al, 2012) such as antihypertensive (Atwal et al, 1989;Atwal et al, 1990), antiinflammatory and antibacterial (Jadhav et al, 2012;Badadhe et al, 2011, Akbas et al, 2010 and antimicrobial (Beena and Akelesh, 2012) were also studied depending on this type of synthesis.…”
Section: ‫ــــــــــ‬ ‫ـــــــــ‬ ‫ــــــــــــــــــــــــــــــــــmentioning
confidence: 99%
“…Biginelli reaction is an efficient one-pot multicomponent condensation reaction that is used widely in organic and medical chemistry (Bose et al, 2005;Kulkarn et al, 2009;Mochaddas et al, 2012). Starting from aldehyde, Urea(thiourea) and β-keto ester under strongly acidic condition represented by Lewis acid to obtaine the pyrimidine-2-one analogs (Kappe, 1993;Mohammadizadeh and Firoozi, 2011), which received a significant attention owing to their biological (Shutalev et al, 1998;Mobinikhaledi and Kalhor, 2010) and pharmaceutical properties (Phucho et al, 2009;Piqani and Zhang, 2011;Shaikh et al, 2012) such as antihypertensive (Atwal et al, 1989;Atwal et al, 1990), antiinflammatory and antibacterial (Jadhav et al, 2012;Badadhe et al, 2011, Akbas et al, 2010 and antimicrobial (Beena and Akelesh, 2012) were also studied depending on this type of synthesis.…”
Section: ‫ــــــــــ‬ ‫ـــــــــ‬ ‫ــــــــــــــــــــــــــــــــــmentioning
confidence: 99%
“…Thiamine hydrochloride (CAT-40) at 5 mol% under ultrasound irradiation with water as the solvent gave the best yields (>47%) for the Biginelli adducts (Table 8) [51]. Furthermore, Badadhe and collaborators reported that the use of CAT-40 (10 mol%) under solvent-free and microwave irradiation conditions afforded the Biginelli adducts in good-to-excellent yields (>82%) [52]. In both works, the authors confirmed the need for a catalyst in the Biginelli reaction because no formation of Biginelli adducts was observed in the absence of CAT-40.…”
Section: Continuedmentioning
confidence: 99%
“…Quinazoline nucleous considered one of the most important classes of pharmaceuticals, which exhibit various activities as anti-tumor [1,2], antimalarial [3], anti-inflammatory [4], and antimicrobial [5,6]. It occurs extensively in nature and range of natural building blocks as alkaloids, and found across the plant and animal kingdoms as well as various microorganisms such as Peganum nigellastrum [7], Bouchardatia neurococca [8], Dichroa febrifuga [9] and Bacillus cereus [10].…”
Section: Introductionmentioning
confidence: 99%